2020
DOI: 10.1186/s12866-020-1701-6
|View full text |Cite
|
Sign up to set email alerts
|

Marine bacterial communities in the upper gulf of Thailand assessed by Illumina next-generation sequencing platform

Abstract: Background: The total bacterial community plays an important role in aquatic ecosystems. In this study, bacterial communities and diversity along the shores of the Upper Gulf of Thailand were first characterized. The association between bacterial communities and types of land use was also evaluated. Results: The bacterial communities and diversity of seawater in the Upper Gulf of Thailand, with regard to types of land use, were first revealed by using Illumina next-generation sequencing. A total of 4953 OTUs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…Members of the SUP05 clade reported in marine waters and are supposed to contribute directly by the successive reduction of nitrate (NO 3 − ) to nitrogenous gases (N 2 O or N 2 ) [80]. Various studies have also identified the occurrence of these genera in algae and surrounding seawater [22,50,81]. Our study results are in agreement with Wei et al, who identified similar profile of bacterial communities in P. yezoensis and surrounding seawater by 16S rRNA gene sequencing approach [82].…”
Section: Bacterial Community Structure and Abundancesupporting
confidence: 91%
“…Members of the SUP05 clade reported in marine waters and are supposed to contribute directly by the successive reduction of nitrate (NO 3 − ) to nitrogenous gases (N 2 O or N 2 ) [80]. Various studies have also identified the occurrence of these genera in algae and surrounding seawater [22,50,81]. Our study results are in agreement with Wei et al, who identified similar profile of bacterial communities in P. yezoensis and surrounding seawater by 16S rRNA gene sequencing approach [82].…”
Section: Bacterial Community Structure and Abundancesupporting
confidence: 91%
“…2016). Nimnoi and Pongsilp (2020) reported that the run‐off water from aquaculture sites significantly affected the community richness and diversity of marine bacteria. In recirculating aquaculture systems, the bacterial community was more diverse in a normal system than in a system with fish disease syndromes (Xue et al .…”
Section: Resultsmentioning
confidence: 99%
“…Next-generation sequencing (NGS) using Illumina is the most widely applied technique in metagenomic studies for analyzing microbial diversity and functional analysis profiles (Jatmiko et al 2019). NGS is the most effective approach technology for individual classification to particular taxa and allowed finer characterization of bacterial genomes as well as deeper taxonomic recognition of complex microbiomes (Nimnoi and Pongsilp 2020). The hypervariable V3-V4 region in the 16S rRNA gene is a target of PCR amplification that can provide information about the bacterial community profile more accurately than the hypervariable V1-V3 region (Teng et al 2018).…”
Section: Discussionmentioning
confidence: 99%